An evaluation of on the job training [İşletmelerde meslek eǧitimi uygulamasina yönelik bir deǧerlendirme] - (:unkn) unknown (My University, 2008)
Labour force training at Vocational and Technical Schools is based on cooperation between school and industry. In this training, the students receive their theoretical education at schools from their teachers while receiving their practical education in industry from professionals and educators. The success of the training is to be achieved by providing a close relationship between all partners that take part in this type of education. In this study, an evaluation of on the job training that is realized at Vocational and Technical Schools has been done for Sisli Vocational High School. For the study, three different type of questionnaire has been prepared and applied on 191 students whose in their 3 rd year and from electrical and electronics department, 36 electrical and electronics teacher and 73 companies that students take their practical education. Data obtained from the questionnaires processed by means of statistical software and analyzed. According to the findings, relation between industries and schools has to be validated, co-operation is to be increased and made more effective.
Keywords: Article 3308; On the job training; Vocational education